Dimensions of Globalization in the Higher Education Curriculum: Content Analysis of the Education Study Program Curriculum at Raden Fatah State Islamic University Palembang. - Azzahra, Radhita; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
This article explores the dynamics of Islamic education politics in the context of globalization, focusing on curriculum development in the Education Study Program at UIN Raden Fatah Palembang. Using literature review and descriptive analysis, the study reveals that globalization demands higher education curricula, especially at UIN Raden Fatah, to integrate both global and national standards, such as the Indonesian National Qualifications Framework (KKNI) and National Higher Education Standards. The curriculum must equip students with scientific and technological skills while preserving Islamic values and local wisdom, such as Malay culture. The main challenge is balancing adaptation to global demands with the preservation of Islamic identity, amidst concerns that globalization may erode local values. In conclusion, curriculum development at UIN Raden Fatah should be adaptive and inclusive to produce globally competent graduates who retain their Islamic character and local cultural identity.